Supply frequency of concentrate as supplement in sugarcane (Saccharum officinarum) forage diets and its effect on the productive performance of Holstein crossbred bulls - Rodr?guez, Dunieski; Martin, Pedro C.; Alfonso, F.; Enr?quez, Ana Valeria; Sarduy, Luc?a (Cuban Journal of Agricultural Science, 2013)
Eigth crossbred bulls Holstein x Zebu, of 315 kg average liveweight, located in two treatments with four repetitions each and random block design were used to study the effect of the supply frequency of concentrate on the productive performance of the animals. The treatments were: A) supply sugarcane forage, mixed with molasses-urea at 2 %, in a feeder once a day; B) supply the forage in separate feeders, twice a day. The experiment was conducted for 64 d. At the end, 368 and 376 kg of liveweight was proved for the treatments A and B, respectively. Analysis of variance according to completely randomized design was carried out. No differences between treatments were found for the indicators of daily mean gain (840-950 g) and DM intake (9.31-9.12 kg), respectively. There was better (P < 0.01) feed conversion (9.6 kg for gaining 1 kg of liveweight) when the concentrate was offered twice a day, in respect to that obtained when supplying it once (11.06 kg). It is concluded that supplying the concentrate twice a day allowed higher efficiency on using the feeds. Key words: fattening, conversion, intake, efficiency, gain.